Odpowiedź :
a) [tex]3\frac{3}{4} + 2\frac{1}{7} = 3\frac{21}{28} + 2\frac{4}{28} = 5\frac{25}{28}[/tex]
b) [tex]6\frac{3}{4} - 4\frac{1}{3} = 6\frac{9}{12} - 4\frac{4}{12} = 2\frac{5}{12}[/tex]
c) [tex]5\frac{4}{15} - 1\frac{2}{5} = 4\frac{19}{15} - 1\frac{6}{15} = 3\frac{13}{15}[/tex]
d) [tex]4\frac{3}{8} + 5\frac{5}{6} = 4\frac{9}{24} + 5\frac{20}{24} = 9\frac{29}{24} = 10\frac{5}{24}[/tex]
e) [tex]8\frac{3}{5} - 3\frac{1}{4} = 8\frac{12}{20} - 3\frac{5}{20} = 5\frac{7}{20}[/tex]
f) [tex]7\frac{10}{21} + 2\frac{9}{14} = 7\frac{20}{42} + 2\frac{27}{42} = 9\frac{47}{42} = 10\frac{5}{42}[/tex]
g) [tex]4\frac{1}{11} + 3\frac{1}{33} = 4\frac{3}{33} + 3\frac{1}{33} = 7\frac{4}{33}[/tex]
h) [tex]3\frac{5}{9} - 1\frac{1}{2} = 3\frac{10}{18} - 1\frac{9}{18} = 2\frac{1}{18}[/tex]
i) [tex]5\frac{6}{7} - \frac{3}{4} = 5\frac{24}{28} - \frac{21}{28} = 5\frac{3}{28}[/tex]